2021
DOI: 10.11591/ijphs.v10i1.20524
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact among health workers in effort to facing the COVID-19 in Indonesia

Abstract: The coronavirus disease (COVID-19) pandemic in Indonesia has a psychological impact among health workers who are working in hospital and caring for patients with positive COVID-19. This study aimed to examines the psychological impact among health workers in effort to facing the coronavirus pandemic (COVID-19) in Indonesia. Snowball sampling technique was employed to gather the sample in the eight islands. The health workers were responded to the depression anxiety stress scales (DASS-42) questionnaire, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
2
12
0
1
Order By: Relevance
“…This further corroborates the findings of previous studies that demonstrated a strong relationship between QOL and education [6], [20], [21]. However, because of COVID-19 pandemic extending over more than a year, the pandemic hit economies and health globally and impacted all the layers across societies [22]- [27]. For nationality, it is understandable that foreign workers (in this case, the non-Malaysian) have additional financial and legal obligations compared to the local worker, which puts them under more environmental pressures.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This further corroborates the findings of previous studies that demonstrated a strong relationship between QOL and education [6], [20], [21]. However, because of COVID-19 pandemic extending over more than a year, the pandemic hit economies and health globally and impacted all the layers across societies [22]- [27]. For nationality, it is understandable that foreign workers (in this case, the non-Malaysian) have additional financial and legal obligations compared to the local worker, which puts them under more environmental pressures.…”
Section: Resultssupporting
confidence: 91%
“…The QOL survey results were converted into percentages where a domain was excluded from the count if the worker did not answer more than one question in that domain, as per the instructions of the WHO. The quality of life scale was calculated for each of the four domains, and the scale was categorized as: very poor (0-20), poor (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), neither poor nor good (41-60), good (61-80), and very good (81-100).…”
Section: Discussionmentioning
confidence: 99%
“…About two thirds (n = 98) of the studies reported the data on depression [ 8 , 23 – 27 , 29 – 33 , 35 , 36 , 38 – 41 , 45 – 52 , 56 – 60 , 62 – 65 , 67 – 69 , 71 – 76 , 78 – 82 , 84 , 86 , 88 , 89 , 91 , 92 , 94 , 95 , 97 , 99 , 100 , 103 , 104 , 106 – 108 , 111 , 113 , 115 – 117 , 120 , 123 , 124 , 127 , 129 – 133 , 137 , 138 , 140 , 141 , 143 – 146 , 149 , 151 – 154 ,…”
Section: Resultsmentioning
confidence: 99%
“…There were 40 studies which reported on data regarding stress, using five different type of scales which were Depression-Anxiety-Stress Scale-21 (DASS-21), Safety Attitudes Questionnaire (SAQ), Perceived Stress Scales (PSS), Stanford Acute Stress Reaction Questionnaire (SASRQ), and State and Trait Anxiety Inventory (STAI) [ 30 , 31 , 39 , 56 , 59 , 77 , 78 , 91 , 92 , 99 – 102 , 104 , 106 , 107 , 113 , 120 , 123 , 124 , 127 , 129 – 133 , 138 , 140 , 141 , 143 , 144 , 150 , 152 , 153 , 155 , 160 , 161 , 164 , 165 ].…”
Section: Resultsmentioning
confidence: 99%
“…6 Hal yang sama ditemukan oleh Nasrullah, dkk (2020) terhadap 644 tenaga medis di Indonesia sebanyak 55 % mengalami tekanan karena merebaknya Covid-19, sebanyak 0,8% mengalami kecemasan dan 34,5% mengalami stres ringan. 7 Perawat sebagai tenaga medis yang langsung terlibat dalam merawat pasien Covid-19 sangat berisiko mengalami stres. 8,9 Tingginya tingkat stres dapat mengakibatkan seseorang mudah lelah, kurang tidur, sedikit waktu bersama keluarga, bahkan terasing dari keluarga.…”
Section: Pendahuluanunclassified